THU0168 A MATCHING-ADJUSTED INDIRECT COMPARISON (MAIC) OF UPADACITINIB VERSUS TOFACITINIB IN CSDMARD-IR PATIENTS WITH MODERATE TO SEVERE RHEUMATOID ARTHRITIS (RA). (June 2019) - Edwards, Christopher; Sawant, Ruta; Du, Ella; Cammarota, Jordan; Tang, Patrick; Garg, Vishvas; Friedman, Alan; Betts, Keith
Abstract : Background: Upadacitinib (UPA), a JAK1 selective inhibitor, is being investigated as monotherapy and combination therapy with DMARDs for the treatment of moderate-to-severe RA. To date, no head-to-head trials have compared the effectiveness of UPA with tofacitinib (TOFA). Objectives: To compare the efficacy of UPA 15 mg monotherapy and combination therapy with TOFA 5 mg combination therapy using MAICs. Methods: Two MAICs were conducted. MAIC is an indirect comparison technique that utilizes individual patient data (IPD) for one treatment and aggregate data for the other treatment to provide comparative evidence after balancing differences in patient characteristics. The first MAIC used IPD from the SELECT-MONOTHERAPY trial of UPA monotherapy vs. methotrexate (MTX) and published data from the Oral Standard trial 1 of TOFA+MTX vs. MTX. The second used IPD from the SELECT-COMPARE trial of UPA+MTX vs. adalimumab (ADA)+MTX and published data from the ORAL Strategy trial 2 of TOFA+MTX vs. ADA+MTX. UPA monotherapy was not compared to TOFA monotherapy based on feasibility analysis and trial selection criteria. Patients in the UPA trials were re-weighted based on age, gender, race, swollen joint count 66/28, tender joint count 68/28, C-reactive protein (CRP), and patient's global assessment, to match the baseline characteristics in each comparator trial. After matching, ACR20/50/70 and clinical remission (SDAI(CRP)≤3.3, CDAI≤2.8, DAS28-ESR/CRP<2.6) were compared for UPA monotherapy vs. TOFA+MTX relative to MTX at month 3 and UPA+MTX vs. TOFA+MTX relative to ADA+MTX at month 3 and 6 using a Wald test. Results: After matching, baseline characteristics were balanced across the trial populations. At month 3, UPA monotherapy patients experienced significantly greater improvement in ACR70 compared to TOFA+MTX with a mean difference in difference (DD) of 9.9% (p<0.05) (Figure 1a ) while UPA+MTX was associated with a higher ACR50 compared to TOFA+MTX with a DD of 12.9% (p<0.05). At month 6, UPA+MTX patients experienced significantly larger improvement in SDAI/CDAI/DAS28-ESR clinical remission compared to TOFA+MTX with DDs of 9.1% (p<0.05), 7.5% (p<0.05), and 11.3% (p<0.01), respectively (Figure 1b ). Conclusion: The results from MAICs indicate that treatment with UPA 15 mg when used as monotherapy or in combination with MTX appears to produce improved outcomes at 3/6 months as compared to TOFA 5 mg+MTX (mono: ACR70 and combination: ACR50, SDAI, CDAI and DAS28-ESR remission). References: [1] van Vollenhoven RF, et al. "Tofacitinib or adalimumab versus placebo in rheumatoid arthritis." NEJM 367.6 (2012): 508-519. [2] Fleischmann R, et al. "Efficacy and safety of tofacitinib monotherapy, tofacitinib with methotrexate, and adalimumab with methotrexate in patients with rheumatoid arthritis (ORAL Strategy)." The Lancet 390.10093 (2017): 457-468. Acknowledgement: The design, study conduct, and financial support for the study were provided by AbbVie. AbbVie participated in the interpretation of data, review, and approval of this publication. Disclosure of Interests: Christopher Edwards Grant/research support from: Abbvie, BMS, Biogen, Celgene, Fresenius, Janssen, Lilly, Mundipharma, Pfizer, MSD, Novartis, Roche, Samsung, Sanofi, UCB, Consultant for: Abbvie, BMS, Biogen, Celgene, Fresenius, Janssen, Lilly, Mundipharma, Pfizer, MSD, Novartis, Roche, Samsung, Sanofi, UCB, Speakers bureau: Abbvie, BMS, Biogen, Celgene, Fresenius, Janssen, Lilly, Mundipharma, Pfizer, MSD, Novartis, Roche, Samsung, Sanofi, UCB, Ruta Sawant Shareholder of: AbbVie, Employee of: AbbVie, Ella Du Employee of: Analysis Group, Inc., which has received consultancy fees from AbbVie to conduct this study, Jordan Cammarota Employee of: Analysis Group, Inc., which has received consultancy fees from AbbVie to conduct this study, Patrick Tang Employee of: Analysis Group, Inc., which has received consultancy fees from AbbVie to conduct this study, Vishvas Garg Shareholder of: AbbVie, Employee of: AbbVie, Alan Friedman Shareholder of: AbbVie, Employee of: AbbVie, Keith Betts Employee of: Analysis Group, Inc., which has received consultancy fees from AbbVie to conduct this study